Perbanyakan Beberapa Jenis Anggrek Melalui Teknik Kultur Jaringan dan Analisis Keanekaragaman Genetik Berdasarkan Penanda RAPD - Gasper Gaman; Nouke Lenda Mawikere; Barahima Abbas (Cassowary, 2018)
Papua is the habitat of a variety of orchids and several of orchid species are endemic in Papua. Diversity of orchid species in Papua is a natural resource which needs special attention in conservation efforts and cultivation. The aimes of this research were determined the suitable medium for in vitro propagation technique of several orchid species which endemic in Papua and determine the genetic diversity of five orchids species using RAPD markers. The research was carried out by cultivation of five edemism orchid species on MS medium which enriched 0 to 40% coconut water. Genetic diversities of five orchid species were determined by using RAPD markers. Results of research showed that overall of orchid were cultured can grow to planlet formation. The suitable medium for growing orchids based on this experiment was Murashige and Skoog (MS) medium that enriched with 40% coconut water. Molecular analysis using RAPD markers showed that the five species of Papua orchid were tested different from another. UPGMA grouping based on the polymorphic bands show that the five species of orchid studied were devided into three groups on the coefficient of 0.4 or 40% their genomic different.